Isolasi dan Karakterisasi Flavonoid dari Daun Belimbing (Averrhoa carambola Linn.L) - Rido Ardianto; Yustini Ma’aruf; Sri Benti Etika (Jurnal Periodic Jurusan Kimia UNP, 2013)
Research of isolation and characterization of flavonoids from the leaves of star fruit (Averrhoa carambola Linn.L) has been done. A 393 g of condensed methanol extracts obtained from 5 kg of fresh leaves starfruit. The methanol extract of hot water added, further fractionated successively with n-hexane and ethyl acetate, resulting in a 4000 ml n-hexane fraction and 5000 ml of ethyl asetat. The flavonoid phytochemical test from the fractionation showed negative fraction of n-hexane, ethyl acetate fraction and water fraction flavonoid positive. Results separation by column chromatography ethyl acetate fraction concentrated extract produced 6 fractions, namely fraction A, B, C, D, E and F. Characterization using UV light gives a brown before chromatograms steamed green ammonia and gives a dark brown color after steamed with ammonia. Based on the existing literature is suspected in fraction B contained flavones glycosides, biflavonil or unusual tersulih flavons.